Risk of Neurodegenerative Diseases in Patients With Acromegaly: A Cohort Study. (25th October 2022) - Hong, Sangmo; Han, Kyungdo; Kim, Kyung-Soo; Park, Cheol-Young
Abstract : Background and Objectives: A few recent studies have reported an association between insulin-like growth factor-1 (IGF-1) and neurodegenerative disease, but there was no report on any association between acromegaly and neurodegenerative disease. We investigated whether the risk of Alzheimer disease (AD), Parkinson disease, and other neurodegenerative diseases was increased among patients with acromegaly using nationwide data of Korea. Methods: We studied the association between acromegaly and Parkinson disease and dementia in 1, 611 patients with acromegaly and controls (age-matched and sex-matched 8, 055 participants with no diagnosis of acromegaly) from the National Health Insurance System database between 2006 and 2016 with a mean follow-up period of 7.34 years. Cox proportional hazards regression analysis was used to assess the risk of all outcomes in patients with acromegaly compared with controls with adjusting for age, sex, household income, place, type 2 diabetes, hypertension, and dyslipidemia. Results: The average age of the patients with acromegaly and the controls was 54.16 years (40.4% men). The incidence rate of Parkinson disease in patients with acromegaly (1.54 per 1, 000 person-years) was significantly higher than that in the control group (0.55 per 1, 000 person-years) (log-rank test p = 0.001). Acromegaly was associated with a higher risk of Parkinson disease (hazard ratio [HR] = 2.609, 95% CI: 1.410–2.609) than the control. In addition, acromegaly was associated with a higher risk of all-cause dementia (HR = 2.299, 95% CI: 1.362–3.881), Alzheimer disease (HR = 2.228, 95% CI: 1.191–4.168), and non-AD dementia (HR = 6.553, 95% CI: 1.754–24.482) than the control during the first 3 years after diagnosis and treatment. In subgroup analysis, diabetes was associated with higher risk of all-cause dementia (P for interaction = 0.028) in patients with acromegaly compared with controls. Discussion: Our study results suggest that acromegaly is associated with neurodegenerative disease. Further study is needed on the association between IGF-1/growth hormone level and neurodegenerative disease.